21. YILINDA HOCALI OLAYLARI - Sarıahmetoğlu, Nesrin (Fırat University, 2013)
Bundan 21 yıl önce Hocalı’da meydana gelenler Azerbaycan tarihinin kanlı ve akıllardan silinmeyecek bir bölümünü meydana getirmektedir. Hocalı Olaylarını anlayabilmek için Azerbaycan’ın yakın dönem tarihi içinde 19-20 yıllık bir dönemin çok iyi değerlendirilmesi gerekir. Bu çalışmada Dağlık Karabağ Savaşı içinde şehir tipli bir kasaba olan ve Ermeniler tarafından işgal edilirken büyük bir facianın yaşandığı devir değerlendirilecektir.

What happens 21 years ago in Khojaly constitute bloody and a part of unforgettable history of Azerbaijan. The near-term 19-20 year period in the history of Azerbaijan needs to be evaluated very well in order to understand Khojaly events. In this study, the period that experienced a major disaster will be evaluated in a city-type small town was being occupiedby the Armenians in the Nagorno-Karabakh War. As it seen that Khojaly events are inseparable part of Nagorno-Karabakh War and have taken place as “Khojaly Tragedy” or “Khojaly genocide” in the histrory of Azerbaijan. As a result of these events Khojaly people live in 48 different regions of Azerbaijan, especially in Baku. Although the difficulties they are enduring and the years have passed they are carrying the hope that undoubtly one day they will return to their territories
Twenty-First Anniversary of Khojaly Events